(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2023)
This study aims to investigate the significance of adopting the best strategic alternatives when applying the evaluation and measurement system for the general secondary stage in Libya, as the optimal measurement evaluation system does not measure the levels of students using traditional strategies, but rather it must measure the scientific and cognitive abilities and skills of the student and the teacher, and then evaluate and develop the process curricula. The study used the analytical descriptive approach, and it concluded with several results, the most important of which is the absence of the main strategic alternatives for the evaluation and measurement system, which is the strategy of diversification of the evaluation and measurement methods, the strategy of focusing on the accuracy of the standards of the evaluation and measurement methods, and the strategy of developing the evaluation and measurement methods, which makes the traditional evaluation and measurement system defective, and it does not achieve the goals for which it was designed.